Avoiding Anomalies of GDP in Constant Prices by Conversion to Chained Prices: Accentuating Shifts in Philippine Economic Transformation - Jesus C. Dumagan (Philippine Institute for Development Studies (PIDS), 2008)
Changing the base year (1985) of Philippine GDP in constant prices could change the growth rate and the shares of components even when there is no change in the volume of production, implying that the changes in growth rate and shares are anomalous (i.e., no real basis). This possibility weakens GDP in constant prices as basis for valuing our economy's production and analyzing its growth performance. This paper demonstrates that conversion to chained prices avoids the above anomalies and also shows smaller and shrinking agriculture and industry sectors and enlarging services sector that is now over 50 percent of the Philippine economy than are shown by valuation in constant 1985 prices. In both contributions to level and growth of GDP, chained prices accentuate more than constant 1985 prices the declining importance of agriculture and industry and the rising importance of services in Philippine economic transformation.
Keywords: C43; 330; real GDP; constant prices; chained prices; Fisher index; Nationaleinkommen; Index; Philippinen